CO2 evasion along streams driven by groundwater inputs and geomorphic controls. Issue 11 (November 2018) - Duvert, Clément; Butman, David; Marx, Anne; Ribolzi, Olivier; Hutley, Lindsay
Abstract Headwaters are hotspots of carbon dioxide (CO2 ) evasion from rivers. While emerging evidence suggests that groundwater contributes disproportionately to CO2 in headwater streams, the processes of CO2 delivery to streams and subsequent evasion to the atmosphere remain largely unknown. Here we show the variability of CO2 input and evasion fluxes based on coupled measurements of dissolved CO2 along streams and in adjacent groundwater from two headwater catchments of the tropical and temperate zones. We find that the processes can be highly localized in both space and time. Spatially, they are significantly influenced by heterogeneities in the subsurface and stream landscape; temporally, they predominately occur during the transient activation of connected subsurface water flows. We highlight sharp increases and decreases in the stream CO2 flux, and suggest that current models fail to capture the true magnitude of CO2 evasion. The high spatial and temporal variability of CO2 input from groundwater and evasion to the atmosphere makes accurate assessment of CO2 evasion fluxes difficult, and will require a collaborative effort by catchment hydrologists and aquatic ecologists to fully understand the contribution of groundwater to stream CO2 emissions. Groundwater-derived CO2 inputs and emissions along streams are highly variable in both space and time, according to measurements of dissolved CO2 from two headwater catchments.